2021
DOI: 10.1039/d0cp06695h
|View full text |Cite
|
Sign up to set email alerts
|

3D phase diagrams and the thermal stability of two-component Janus nanoparticles: effects of size, average composition and temperature

Abstract: Determining binary phase diagrams for nanoparticles proves to be a very difficult task regardless if it is tried either by computer simulations, theoretical considerations or experiments. In this work, using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…It was shown that the equilibrium compositions of the phases in Janus nanoparticles change with both the particle’s size and average composition. This means that the use of 3D phase diagrams is required bimetallic nanoparticles . Furthermore, the shape of the phase diagram depended on the interface structure of the two-phase nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the equilibrium compositions of the phases in Janus nanoparticles change with both the particle’s size and average composition. This means that the use of 3D phase diagrams is required bimetallic nanoparticles . Furthermore, the shape of the phase diagram depended on the interface structure of the two-phase nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…We should note that the lever rule is not applicable to nanophase separation diagrams, similarly to a case of melting transitions. , The rule, related to conservation of the elemental atom numbers in the NP, does work for the complementary and less familiar “solubility diagrams”, presenting the equilibrium compositions of the two separated nanophases. , (For macrosystems the two types of diagrams coincide.) In the present case of the Pd–Ir core, average compositions vs temperature have been chosen and obtained by using the site concentrations of the Pd-rich and Ir-rich nanophases (e.g., shown above in Figure a; this choice differs from the solubility definition using maximal and minimal site concentrations). Compared to the bulk alloy, the computed solubility diagrams (Figure a) reveal enhanced miscibility (also observed for Au–Rh), which increases with the NP size decrease.…”
Section: Resultsmentioning
confidence: 99%
“…33,13 (For macrosystems the two types of diagrams coincide.) In the present case of the Pd−Ir core, average compositions vs temperature have been chosen and obtained by using the site concentrations of the Pd-rich and Ir-rich nanophases (e.g., shown above in Figure 6a; this choice differs from the solubility definition using maximal and minimal site concentrations 33 ). Compared to the bulk alloy, the computed solubility diagrams (Figure 10a) reveal enhanced miscibility (also observed for Au−Rh 2 ), which increases with the NP size decrease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations